Efficiency differences in Kansas beef cow-calf production - Stryker, L.; Jones, R.; Langmeier, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
For the beef industry to be economically competitive with other meat industries, it is essential that individual producers strive for the most efficient, highest quality, least cost production possible. A sample of 26 Kansas beef cow-calf enterprises from the Kansas Standardized Performance Analysis database (SPA) was used to measure efficiency differences among producers, as well as factors contributing toward these differences. On average, farms were 86% technical, 69% economic, and 58% overall efficient. Thus, our results suggest that output could be increased by 14% with optimal technology use, and cost could be decreased by 42% if farms were fully economically efficient.
Keywords: Beef; Cow-Calf; Efficiency; Profitability; SPA